Overexpression of Optic Atrophy Type 1 Protects Retinal Ganglion Cells and Upregulates Parkin Expression in Experimental Glaucoma - Hu, Xinxin; Dai, Yi; Zhang, Rong; Shang, Kunte; Sun, Xinghuai (Frontiers in Molecular Neuroscience, 2018)
Glaucoma is a neurodegenerative disease that features progressive loss of retinal ganglion cells (RGCs). Increasing evidences have revealed that impaired mitochondrial dynamics occurs early in neurodegenerative diseases. Optic Atrophy Type 1 (OPA1), a mitochondrial fusion protein, has recently been suggested to be a mitophagic factor. Our previous studies found that glaucomatous retinal damage may be ameliorated by an increase in mitochondrial OPA1. In this study, we explored the mechanism involved in OPA1 mediated neuroprotection and its relationship with parkin dependent mitophagy in experimental glaucoma models. Our data showed that overexpression of OPA1 by viral vectors protected against RGC loss, attenuated Bax expression, and improved mitochondrial health and mitochondrial surface area. Parkin expression and the number of mitophagosomes were upregulated in OPA1 overexpressed RGCs under glutamate excitotoxicity. While knockdown of OPA1 by siRNA decreased protein expression of parkin in RGCs under glutamate excitotoxicity. Two weeks after intraocular pressure (IOP) elevation, the LC3-II/I ratio and the LAMP expression were increased in OPA1 overexpressed optic nerve. These findings suggest that OPA1 overexpression may protect RGCs by ways of enhancing mitochondria fusion and parkin mediated mitophagy. Interventions to promote mitochondrial fusion and mitophagy may provide a useful strategy to battle against glaucomatous RGC loss.